Analisis Kepuasan Pelanggan Menggunakan Metode Algoritma C4.5 Berdasarkan E-Survey Kejaksaan Negeri Minahasa - Mohamad Alparizi Sahadan; Prof. Dr. Ing. Parabelem T. D. Rompas, MT; Cindy P. C. Munaiseche, ST, M. Eng (Program Studi Teknik Informatika, 2023)
Customers in the Minahasa State Prosecutor’s Office are the main thing in service. A customer supports experiencing various levels of satisfaction, namely if the service is not appropriate after being received, then the customer will feel dissatisfied. On the other hand, if the service is in line with expectations, the customer will feel satisfied that one day the customer will use the service. The calcutation method use is the C4.5 algorithm. The software development method used is Prototype. Data collection methods use are observation, literature and interview. Based on the first and second tests, customer satisfaction data on administrative, case, legal, and technical service with 80 training data and 20 testing data for the first test and 90 training data and 10 data testing data for the second test obtained an accuracy result of 90% for administrative service satisfaction, 90% accuracy for case service satisfaction, 90% accuracy for legal service satisfaction and 90% accuracy for technical service satisfaction. So that it can be satisfaction with service based on the e-survey of the minahasa state prosecutor’s office.